Cellular uptake of metallated cobalamins. Issue 3 (7th January 2016) - Tran, Mai Thanh Quynh; Stürup, Stefan; Lambert, Ian Henry; Gammelgaard, Bente; Furger, Evelyne; Alberto, Roger
Abstract : Cellular uptake of vitamin B12-cisplatin conjugates was estimated via detection of their metal constituents (Co, Pt, and Re) by inductively coupled plasma mass spectrometry (ICP-MS). Abstract : Cellular uptake of vitamin B12-cisplatin conjugates was estimated via detection of their metal constituents (Co, Pt, and Re) by inductively coupled plasma mass spectrometry (ICP-MS). Vitamin B12 (cyano-cob(iii )alamin) and aquo-cob(iii )alamin [Cbl-OH2 ] +, which differ in the β -axial ligands (CN − and H2 O, respectively), were included as control samples. The results indicated that B12 derivatives delivered cisplatin to both cellular cytosol and nuclei with an efficiency of one third compared to the uptake of free cisplatin cis -[Pt II Cl2 (NH3 )2 ]. In addition, uptake of charged B12 derivatives including [Cbl-OH2 ] +, [Co-CN-{ cis -PtCl(NH3 )2 }] +, [Re-Co-CN-{ cis -PtCl(NH3 )2 }] +, and [Co-CN-{ trans -Pt(Cyt)(NH3 )2 }] 2+ (Cyt = cytarabin) was high compared to neutral B12, which implied the existence of an additional internalization pathway for charged B12 vitamin analogs. The affinities of the charged B12 derivatives to the B12 transporters HC, IF and TC were similar to that of native vitamin B12.